Metabolic reprogramming in viral infections: the interplay of glucose metabolism and immune responses - Darweesh, Mahmoud; Mohammadi, Saeed; Rahmati, Mina; Al-Hamadani, Moosa; Al-Harrasi, Ahmed (Frontiers in Immunology, 2025)
Metabolic reprogramming is an important player within the immune response to viral infections, allowing immune cells to fine-tune their energy production and biosynthetic requirements while it is actively working to restrict pathogen access to essential nutrients. Particularly, glucose metabolism, which appears to be one of the important regulators of immune function, affects immune cell activation, cytokine secretion, and pathogen restriction. This review explores the mechanisms of metabolic reprogramming during viral infections, with a specific emphasis on glucose metabolism. We discussed the key cytokines involved in orchestrating this metabolic process and the influence of pre-existing metabolic disorders on immune efficiency. Furthermore, we introduced emerging therapeutic strategies that target glucose metabolism to enhance antiviral immunity and improve disease outcomes. A deeper understanding of the interaction between metabolism and immunity could be promising for the development of novel immunometabolic targets against viral infections.